Epigenetic Consequences of in Utero Exposure to Rosuvastatin Alteration of Histone Methylation Patterns in Newborn Rat Brains - Dulka Karolina (INTERNATIONAL JOURNAL OF MOLECULAR SCIENCES, 2021)
Rosuvastatin (RST) is primarily used to treat high cholesterol levels. As it has potentially harmful but not well-documented effects on embryos, RST is contraindicated during pregnancy. To demonstrate whether RST could induce molecular epigenetic events in the brains of newborn rats, pregnant mothers were treated daily with oral RST from the 11th day of pregnancy for 10 days (or until delivery). On postnatal day 1, the brains of the control and RST-treated rats were removed for Western blot or immunohistochemical analyses. Several antibodies that recognize different methylation sites for H2A, H2B, H3, and H4 histones were quantified. Analyses of cell-type-specific markers in the newborn brains demonstrated that prenatal RST administration did not affect the composition and cell type ratios as compared to the controls. Prenatal RST administration did, however, induce a general, nonsignificant increase in H2AK118me1, H2BK5me1, H3, H3K9me3, H3K27me3, H3K36me2, H4, H4K20me2, and H4K20me3 levels, compared to the controls. Moreover, significant changes were detected in the number of H3K4me1 and H3K4me3 sites (134.3% +/- 19.2% and 127.8% +/- 8.5% of the controls, respectively), which are generally recognized as transcriptional activators. Fluorescent/confocal immunohistochemistry for cell-type-specific markers and histone methylation marks on tissue sections indicated that most of the increase at these sites belonged to neuronal cell nuclei. Thus, prenatal RST treatment induces epigenetic changes that could affect neuronal differentiation and development.